Customary Marriage Registration in Realizing Legal Certainty in Indonesia - Dina Paramitha Hefni Putri; Ekawati; Gusti Heliana Safitri (Faculty of Law, Universitas Pekalongan, 2024)
This study examines the legal issues arising from the unregistered customary marriage, a fundamental issue in the balance between local wisdom and state regulations. On the one hand, customary marriage is an institution that contains socio-cultural values ​​and community identity that have long existed, while on the other hand the informality of the marriage registration raises various legal issues, including unclear legal status, protection of inheritance rights, and access to socio-bureaucratic facilities. The absence of official registration triggers a conflict between positive legal norms and religious and customary values ​​that are still upheld, thus creating a gap in the enforcement of rights and obligations at the local and national levels. In addition, the phenomenon of marriage without official registration also has an impact on vulnerable groups, such as adolescents, who are at risk of experiencing abuse of rights and minimal legal protection. The research method used is normative legal research with a literature approach, considering that the data processed are in the form of laws and regulations and scientific literature. The results of the study indicate that the integration of customary law and positive law through the active role of institutions such as the Office of Religious Affairs and the Population and Civil Registration Service is a strategic step to synergize the two systems, so that it can provide comprehensive legal certainty for the recognition of rights, clarity of marital status, protection of inheritance, and guarantee of access to administrative facilities. Inclusive legal reform and increasing socialization and human resource competence are the keys to reconciling local traditions with modern legal requirements in order to realize social justice and protection of citizen rights).